The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.17475/kujff.70812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stocking Rate on Forage Availability and Growth Performance of Goat Kids in Mediterranean Kermes Oak Shrublands

Abstract: This study aims to investigate the effect of stocking rate on forage availability (vegetation cover (VC) and forage mass (FM)) and the growth performance of pure hair goat kids (Capra hircus L.) in Mediterranean Kermes oak shrublands. Two villages that had the same ecological conditions but where the presence of pure hair goats did or did not exceed the grazing capacity were selected specifically within this scope. The birth weight (BW) and the daily live weight gain at 90 days (DLWG at 90 days) of pure hair g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…At this point, the damage that they cause to young saplings comes to the forefront. It is reported that young saplings have deformations and structural defects in forestry due to the effect of climbing of ruminants and this situation inhibits the growth of saplings (Türkoğlu et al, 2016). Uncontrolled goat grazing is reported to have negative effects on forest regeneration and maquis in the Mediterranean region, where the growth of most saplings is typically slow because of the undesirable impact of ungulates (Lovreglio et al, 2014;San Francisco Estuary Institute [SFEI], 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the damage that they cause to young saplings comes to the forefront. It is reported that young saplings have deformations and structural defects in forestry due to the effect of climbing of ruminants and this situation inhibits the growth of saplings (Türkoğlu et al, 2016). Uncontrolled goat grazing is reported to have negative effects on forest regeneration and maquis in the Mediterranean region, where the growth of most saplings is typically slow because of the undesirable impact of ungulates (Lovreglio et al, 2014;San Francisco Estuary Institute [SFEI], 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It can be considered that it is an important source of roughage for goats, especially if the pasture areas of sufficient quality and quantity are limited. Türkoğlu et al (33) reported that there is a very strong positive relationship between growth performance of grazing hair goats and the feed mass of the kermes oak. Kamalak et al (13) reported that oak leaves are rich in CP, CA, NDF, ADF and condensed tannin.…”
Section: Introductionmentioning
confidence: 99%